Notes about folk edition on social networks - Conti, Tamires Cristina Bonani; Almeida, Terezinha Ferreira de (Revista da ABRALIN, 2023)
In this paper, we aim to reflect about the practice that has become a theme of an Instagram page: the rewriting of journalistic news, so that the headline appears erased with red pen, adapting it paradigmatically to the ideological position of its folk editor. Thus, for such, we based ourselves on Almeida’s reflections (2021), being used the theoretical-methodological contribution of the French-oriented Discourse Analysis, more specifically of Maingueneau (2008), in an integrative proposal with Folk Linguistics, according to Paveau (2008). Our main results indicated that such folk intervention goes beyond the linguistic field, acting also as a folk judicial intervention.